2009
DOI: 10.1016/j.chemphyslip.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in the formation of conjugated linoleic acids from thermally induced 9t12t linoleic acid: a study by gas chromatography and infrared spectroscopy

Abstract: Thermally induced isomerisation leading to the formation of Conjugated Linoleic Acids (CLA) has been observed for the first time during the thermal treatment of 9t12t fatty acid triacylglycerol, and methyl ester. Fifteen microlitre portions of the triacylglycerol sample containing 9t12t fatty acid (trilinoelaidin) were placed in micro glass ampoules and sealed under nitrogen, then subjected to thermal treatment at 250 o C. The glass ampoules were removed at regular time intervals, cut open, and the contents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The identity of the relatively large peak in the group was confirmed as methylene interrupted 9t12t (18:2) fatty acid. In an earlier report [23], it was shown that the CLAs can also be formed by thermally inducing a triacylglycerol containing 9t12t fatty acid. Therefore, the formation of 9t12t (18:2) is possible during thermal induction of CLA fatty acids.…”
Section: Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…The identity of the relatively large peak in the group was confirmed as methylene interrupted 9t12t (18:2) fatty acid. In an earlier report [23], it was shown that the CLAs can also be formed by thermally inducing a triacylglycerol containing 9t12t fatty acid. Therefore, the formation of 9t12t (18:2) is possible during thermal induction of CLA fatty acids.…”
Section: Mechanismmentioning
confidence: 99%
“…Therefore, the formation of 9t12t (18:2) is possible during thermal induction of CLA fatty acids. The reaction takes place through an intramolecular [1,3], sigmatropic rearrangement or a free radical chain reaction mechanism [16,23]. The identification of 9t12t led to the inclusion of the [1,3] sigmatropic transformation part in the mechanism presented in Fig.…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other studies have highlighted the formation of conjugated linoleic acids (CLAs) during the heating of edible oils, showing that trans,trans CLA isomers are the predominant products, followed by cis,trans and trans,cis CLA isomers (Christy 2009;Guo et al 2015). Recently, interest in CLAs has increased due to the biological activities associated with their numerous isomers.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry and mechanistic pathways involved in the formation of CLAs were also discussed in the above research reports. Christy [14] has also contributed to supplement the mechanistic aspects by demonstrating that CLA isomers could be produced by thermal induction of 9t12t LA. In a recent report Christy [15] demonstrated that the [1,5] sigmatropic transformations and positional isomerisation could be achieved by subjecting triacylglycerols of CLAs to a suitable high temperature.…”
Section: Introductionmentioning
confidence: 99%